Community and coastal Management in Selangor, Malaysia - Asmawi, M. Zainora; Amer Younus, Mohamad; Hj. Mohd. Noor, Norzailawati (IIUM, 2014)

(untitled)
Malaysia is a maritime nation blessed with invaluable coastlines. With the increase in world population in the coastal cities, there is a strong need to control the adverse effects of global warming and its related effects to the coastal areas. In this regards, the contribution of coastal community is essential to support a livable and sustainable coastal development. Community is one of the key stakeholders in managing coastal areas. As such, this research was initiated to see the roles and contributions of local community in coastal management in Kuala Selangor, Malaysia. Though various researches have been carried out regarding the management of the coastal area, there is still little effort to how best local communities can be equipped at practicing management of the coastal area in Malaysia. The research focuses on analysing the involvement of communities at the local level in coastal protection initiatives along Selangor coastlines in Malaysia, in terms of types of work, the level of contribution and other associated matters. A questionnaire survey method with the sampling size of 271 was employed in gathering primary data on the contribution of local community in the protection of coastlines. The main findings indicate that the local community has moderate level of awareness on the concept of coastal management even though they have great awareness of their roles as the coastal community in protecting the coastal areas. It can be concluded that the local community currently has little knowledge on coastal management but they have high expectation of their potential roles and contribution in supporting the achievement of livable and sustainable development at the coasts.